LIDAL (Light Ion Detector for ALTEA): a compact Time-Of-Flight detector for radiation risk assessment in space. (May 2019) - Rizzo, A; Berucci, C; De Donato, C; Di Fino, L; Lamastra, F R; La Tessa, C; Masciantonio, G; Messi, R; Morone, C; Picozza, P; Rovituso, M; Tommasino, F; et al.
Abstract: Manned space missions towards Moon and Mars planned in the next decades require a reliable radiation risk assessment considering the long time exposure of astronauts (up to years) to different radiation fields. The radiation environment inside a human space habitat, generated by the interaction of the Galactic Cosmic Rays and occasionally of Solar Particle Events with the spacecraft hull, is peculiar due to its composition (ions from Hydrogen to Iron, knock out neutrons) and the large kinetic energy range of the particles. For this reason the risk assessment approach used for astronauts in space is quite different from the one used on Earth. In this approach the risk for astronauts is evaluated calculating factors which score the risk in function of physical characteristics of the single particle, like the quality factor Q (related to the radiation ionizing power) or the squared ratio between the charge (Z) and velocity ( β ) of the particle ( Z 2 / β 2 ). LIDAL-ALTEA (Light Ion Detector for ALTEA - Anomalous Long Term Effects on Astronauts) is an experimental apparatus which will allow to evaluate for the first time in the field the Z 2 / β 2 risk factor of the single detected particle on-board the International Space Station. The LIDAL system is a Time-Of-Flight detector designed to work paired to three Silicon Detector Units of the ALTEA, which will measure the deposited energy of the passing particle. The velocity of the particle ( β ), calculated from the Time-Of-Flight measurement performed by LIDAL, allows to evaluate the particle electric charge once related to the deposited energy measured by ALTEA. A first LIDAL prototype has been developed by the University of Rome "Tor Vergata" and tested at TIFPA (Trento Insistute for Fundamental Physics Applications) proton beam line, in order to evaluate the timing performances of the detector. Results are briefly presented and the current status of the apparatus production is discussed in view of the launch scheduled for 2019.